Interaksi Simbolik Pada Grup Telegram Komunitas Stop Judi Online - Imam Budianto; Frengki Napitupulu (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The rise of online gambling in Indonesia has led to a serious addiction crisis, exposing the limitations of formal institutions in addressing the issue. This study explores symbolic interaction in the “Stop Judi Online” Telegram community and examines how members form new identities through these interactions. Using a qualitative netnographic approach under an interpretive phenomenological paradigm and symbolic interactionism theory, data were collected via participant observation, in-depth interviews, and digital documentation from members. Analysis involved triangulation and staged coding. The community has developed its own symbolic system with terms like “day-1,” “kapok,” and “reset,” which signal identity transformation. Member narratives follow a recurring three-phase cycle: fall, turning point, and recovery serving as a symbolic rehabilitation blueprint. Telegram’s anonymity enables a safe space for honest self-reconstruction. Symbolic interaction fosters identity change through shared meanings. The study suggests integrating this model into formal rehabilitation by adopting anonymity and peer-driven participation.